Effect of Mixing Solvents on the Structure of Trehalose Tri-isostearate Nonionic Surfactant Reverse Micelles - Shrestha, Rekha Goswami; Shrestha, Lok Kumar (Journal of Nepal Chemical Society, 2012)
Effects of mixing fraction of n-decane (Dec) with n-tetradecane (TD) on the shape, size, and internal structure of trehalose tri-isostearate (designated as TQ-3) nonionic surfactant reverse micelles have been investigated using small-angle X-ray scattering (SAXS) technique. TQ-3 self-assembles into a variety of reverse micellar structures in different organic solvents under ambient conditions It was found that a subtle difference in solvent polarity plays a crucial on the structure of reverse micelles. To better understand the solvent dependence of reverse micellar structure, an attempt has been made studying the effects of mixing solvents (alkanes). Three alkanes with different alkyl chain lengths; C10, C12, and C14, were considered and C10 and C14 were mixed in different mixing fractions (wt ratio). SAXS measurements were carried out on 5 wt% TQ-3 systems under ambient conditions. Micellar size and the internal structure (cross-section diameter) were found to depend on mixing fractions of solvents and could be explained in terms of packing parameter. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6438 J. Nepal Chem. Soc., Vol. 27, 2011 26-33 Uploaded date: 16 July, 2012